Does laparoscopy increase the risk of peritoneal recurrence after resection for pT4 colon cancer? Results of a propensity score-matched analysis from an international cohort. Issue 8 (August 2022) - Pedrazzani, Corrado; Kim, Hye Jin; Park, Eun Jung; Turri, Giulia; Zagolin, Gaia; Foppa, Caterina; Baik, Seung Hyuk; Spolverato, Gaya; Spinelli, Antonino; Choi, Gyu Seog
Abstract: Background: Peritoneal metastases (PM) occur in 15–20% of surgically resected pT4 colon cancer (CC) and strongly affect prognosis. Since no standard treatment has been established, efforts should be addressed toward its prevention. Some literature suggests a detrimental effect of laparoscopy in pT4 CC, hence we aimed to determine its impact on the development of PM after potentially curative resection. Methods: International multicenter retrospective cohort study including consecutive patients undergoing surgery for pT4a and pT4b CC (2014–2018) at 5 referral centers. The inclusion criteria were absence of distant metastasis, elective surgery, curative-intent resection (R0-1), and a minimum follow-up of 24 months (median, IQR: 35, 25.8–50.5 months). Results: 276 patients fulfilled the inclusion criteria and were selected for analysis. After 1:1 propensity score matching (PSM), 63 patients in the laparoscopic group (LapGroup) were compared with 63 patients in the open surgery group (OpenGroup). The two groups were comparable in terms of demographic and clinical parameters, operative data, and specimen characteristics. The OpenGroup presented a higher estimated intraoperative blood loss (P < .001) and postoperative length of stay (P < .001). Overall survival, cancer-specific survival, and disease-free survival resulted comparable. The 5-year probability of developing PM was 16.2% after laparoscopy and 19.5% after open surgery (P = .686). Multivariate analysis confirmed laparoscopy not to be an independent risk factor for PM. Conclusions: Elective laparoscopic surgery for pT4 CC does not seem to increase the risk of metachronous PM after potentially curative surgery. Long-term outcomes after laparoscopy are not inferior to conventional open resections.